(untitled) (American Journal of Pedagogical and Educational Research, 2022)
The success of concepts in the social sciences is often measured by the number of academic publications referring to them, by their capacity to cross the boundaries of disciplines and by their penetration into mass media and wider public discourses. If, however, we take qualitative criteria such as the explanatory power of a concept and its precision in distinguishing different social phenomena as indicators for its usefulness in social theory and research, then successful proliferation may diminish academic value.